(3JWhQ EOGQI GdehGQO GdHTQjI (B:s (3Gdeaghe (B-(3GdGSJQGJjLjI (B-(3GdehbY GdJfXjej (B/s - (3GdYRGhj, fLe YHO Gddgs; (3LhGO, YHGS MSjf s ((3YeGf(B: s (3OGQ GdjGRhQj(B, s, 2010)
(3EOGQI GdehGQO GdHTQjI h GdeUWdMGJ GdHOjdI , eGgjI EOGQI GdehGQO GdHTQjI , GdhXjaI GdYGeI h GdhXjaI GdNGUI , GSJQGJjLjI EOGQI GdehGQO GdHTQjI ,JfXje h CgOGa EOGQI GdehGQOGdHTQjI h ehbYgG Ydi Gdgjcd GdJfXjej ddefXeI h GdOhdI eY hLhO CSFdI ddefGbTI h GdGLGfI YfgG(B.s
(3eQGLY U(B.185s
Keywords: (3EOGQI GdCaQGOs; (3GdEOGQI GdYGeIs; (3GdehGQO GdHTQjIs